PERAN GURU DALAM DALAM MENERAPKAN DISIPLIN SISWA PADA PROSES PEMBELAJARAN PKn DI SDN 03 RANDANGAN KABUPATEN POHUWATO - Maryam H. Dumako (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
The formulation of the problem in this research is how the teacher's role in applying student discipline in the Civics learning process in applying student discipline to the learning process at SDN 03 Randangan, Pohuwato Regency. The objectives to be achieved in this study are to determine the role of teachers in applying student discipline in the learning process of Civics at SDN 03 Randangan, Pohuwato Regency. The method used in this research is descriptive qualitative. The data collection techniques are through observation, interviews and documentation as well as data analysis techniques, display data reduction and conclusions. Based on the results of the study that the teacher's role in implementing student discipline in the Civics learning process at SDN 03 Randangan, Pohuwato district, the teacher has a role as a learning resource, facilitator, class manager, demonstrator, mentor, motivator and evaluator. good relations between students and teachers, providing guidance to students who are less disciplined and informing students about their position in school, for example, as students, they must respect teachers and show good discipline. Based on the results of the research and discussion, it can be concluded that the teacher's role in applying student discipline to the Civics learning process at SDN 03 Randangan, Pohuwato district is good.